If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -19 = 6x + 53 Reorder the terms: -19 + 7x = 6x + 53 Reorder the terms: -19 + 7x = 53 + 6x Solving -19 + 7x = 53 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -19 + 7x + -6x = 53 + 6x + -6x Combine like terms: 7x + -6x = 1x -19 + 1x = 53 + 6x + -6x Combine like terms: 6x + -6x = 0 -19 + 1x = 53 + 0 -19 + 1x = 53 Add '19' to each side of the equation. -19 + 19 + 1x = 53 + 19 Combine like terms: -19 + 19 = 0 0 + 1x = 53 + 19 1x = 53 + 19 Combine like terms: 53 + 19 = 72 1x = 72 Divide each side by '1'. x = 72 Simplifying x = 72
| -6x+2=-46 | | 6y-4x=4 | | 5+2x+x=3x-x+8 | | 15x^2-7x-4=0 | | 6-4n=-20 | | 7+2x(3)=4x+9 | | 2f+3=9a-10 | | (6x)7x= | | 4(t-6)+6t=5(2t+4)-8 | | 8+4n=-12 | | Y^2=6Y | | 5*19= | | 5x-19= | | 15+2n=9 | | 7-2(-5x-9)+2x=4(2x-1)+3(x+12) | | -6=24 | | 4-5n=11 | | 24x+27=-36x-6 | | 3y=-72 | | -0.5b+0.44444444444=0.57142857142 | | -6+2x=-4 | | 2y^2-6y+4=0 | | -(6y+2)-(5y-4)=1 | | 4x+13=-78-9x | | 18=7.5h | | 1x-7= | | a^2+3a=2 | | 1.2y=6.84 | | 8-x+5x-3-8x= | | -2x^2+8x+4=0 | | .5(3x+5)=1 | | 5x+4-3x+5+2x-9= |